Interlayer mixing in lithium nickel manganese cobalt oxide cathode materials for rechargeable lithium batteries - Tan Tze Qing (School of Materials Engineering, Universiti Malaysia Perlis, 2014)
Composition of LiNi1/3Mn1/3Co1/3O2 and its analogous Li[(Ni0.5Mn0.5)1-xCox]O2 were prepared by conventional solid state method to evaluate the effects of reducing cobalt contents to the layered rock salt-type cathode materials. Structural analysis usingRietveld refinement of conventional XRD data revealed that the amount of cobalt contents is highly correlated to their structural stability.